Importance of irrigated agriculture to the Ethiopian economy: capturing the direct net benefits of irrigation - Hagos, Fitsum; Makombe, Godswill; Namara, Regassa E.; Awulachew, Seleshi Bekele (International Water Management Institute, 2009)
Irrigation development has been identified as a means to stimulate economic growth and rural development in Ethiopia. However, little attempt has been made to quantify the contribution of irrigation to national income. Using data from selected irrigation schemes, representing small, medium and large-scale schemes of modern or traditional typologies; the present coverage and planned growth of irrigation, actual and expected contributions of irrigation to the national economy were quantified following the approach of adjusted gross margin analysis. Our results show that irrigation yields 219.7% higher income compared to the rainfed system while its current and future contribution to agricultural GDP is estimated to be about 5.7 and 12% although irrigation covers about 5 and 9% of the total cultivated land area, respectively.